An Experimental Investigation the Optimum of Salinity and Ph of Sea-Water to Improve Oil Recovery from Sandstone Reservoir as A Secondary Recovery Process - Madi Abdullah Naser; Mohammed A Samba; Yiqiang Li (Journal of Petroleum and Geothermal Technology, 2020)
Laboratory tests and field applications shows that the salinity of water flooding could lead to significant reduction of residual oil saturation. There has been a growing interest with an increasing number of low-salinity water flooding studies. However, there are few quantitative studies on seawater composition change and it impact on increasing or improving oil recovery.  This study was conducted to investigate only two parameters of the seawater (Salinity and pH) to check their impact on oil recovery, and what is the optimum amount of salinity and ph that we can use to get the maximum oil recovery.  Several core flooding experiments were conducted using sandstone by inject seawater (high, low salinity and different pH). The results of this study has been shown that the oil recovery increases as the injected water salinity down to 6500 ppm and when the pH is around 7. This increase has been found to be supported by an increase in the permeability. We also noticed that the impact of ph on oil recovery is low when the pH is less than 7.